PENERAPAN PRINSIP GOOD GOVERNANCE DALAM PERENCANAAN DAN PEMBANGUNAN JALAN TOL YOGYAKARTA-BAWEN - Trianggraini, Sela Ajeng; Musleh, Moh.; Tamrin, M. Husni; Subianto, Agus (Dinamika Governance: Jurnal Ilmu Administrasi Negara, 2025)
The development of toll road infrastructure is one of the main solutions to overcome congestion problems and improve connectivity between regions in Indonesia. The Yogyakarta-Bawen Toll Road Project is part of the National Strategic Project that aims to accelerate mobility between Yogyakarta and Central Java. This study aims to analyze the application of good governance principles in the planning and construction of the Yogyakarta-Bawen Toll Road project, using the theory put forward by the United Nations Development Programme (UNDP) in 1997. The principles analyzed include transparency, accountability, participation, effectiveness, and sustainability. The method used in this study is a literature study by reviewing related documents and previous research results. The results of the study indicate that although the principles of good governance have been applied in several aspects, such as transparency of information and accountability through periodic reports, challenges still arise in terms of community participation and efficiency of project implementation. Several aspects such as land acquisition and independent supervision also require more attention to accelerate project completion and reduce potential conflicts. This study suggests that the principle of community participation be strengthened and the monitoring mechanism be further improved in order to achieve inclusive and sustainable development success.